Appendiceal Endometriosis Causing Acute Appendicitis in Pregnancy - Arachchilage, Chathura Egoda; Stevens, Sean; Hock, Sarah van der; Richardson, Amy (Archives of Clinical and Medical Case Reports, 2025)
Endometriosis is commonly seen in women of reproductive age, causing infertility and chronic pelvic pain. Endometriosis in pregnancy poses unique obstetric and neonatal risks, which must be carefully managed. A rare yet significant complication is the development of appendiceal endometriosis leading to acute appendicitis. This case report discusses the presentation of a pregnant women in her 30s with Gravida(G1) Parity(P1) in her third trimester diagnosed with appendiceal endometriosis causing acute appendicitis. The patient was managed surgically with a laparoscopic appendectomy and pelvic washout, after careful consideration of the surgical and anaesthetic risks to the mother and 32-week-old foetus. This case report highlights the importance of timely early recognition of acute surgical emergencies in pregnancies, use of ideal imaging modality, timely intervention, judicial use of antibiotics, post operative concerns would change the overall outcome to both mother and the baby.